Factors Associated with High Prevalence of Multibacillary Leprosy in West Bengal: A Case-Control Study - Mukhopadhyay, Dipta Kanti; Sarkar, Tarun Kumar; Chatterjee, Supantha; Ray, Soumalya; Roy, Pritam; Biswas, Asit Kumar (Indian journal of public health, 2024)
Background: High proportion of multibacillary (MB) among newly diagnosed leprosy cases poses a public health challenge. Objectives: This study aimed to find out the factors associated with the high burden of MB leprosy in West Bengal. Materials and Methods: This case-control study was conducted from August 2020 to December 2022 in three high-endemic districts (annual new case detection rate ≥10/lakh) of West Bengal. Objectives: MB cases registered under the National Leprosy Eradication Programme were considered as case and paucibacillary (PB) cases were considered as control. Weighted sample sizes for cases and controls in each of the three districts were selected using simple random sampling from the list of registered leprosy patients. Requisite data were collected through structured interview with a validated questionnaire in Bengali. R, version 4.1.1 (R Foundation for Statistical Computing, 2021, Vienna, Austria) was used for data analysis. A binary logistic regression model was prepared with the type of leprosy as a dependent variable. Results: Three hundred and ninety-eight individuals, 204 MB and 194 PB, participated in this study with 1.97% nonresponse rate. Gender, marital status, and diagnostic delay (adjusted odds ratio = 2.75 [1.66,4.65]) were associated with developing MB. Not perceiving the symptoms seriously (90, 56% [PB], 97, 51% [MB]), lack of knowledge about the disease and its complications (47, 29% [PB], 53, 28% [MB]), delayed referral by the private practitioners (11, 7% [PB], 22, 12% [MB]) were the major reasons of delay. Conclusion: This study identified a vulnerable group - married and migrated males. Changing from annual screening to quarterly screening along with capacity building and awareness generation of the targeted population is the need of the hour for eradicating the disease.